2002
DOI: 10.1046/j.0019-2805.2001.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological characterization of a γδ T‐cell stimulatory ligand on autologous monocytes

Abstract: SUMMARYBovine cd T cells are stimulated to proliferate by autologous monocytes. This is referred to as the autologous mixed leucocyte reaction (AMLR). It has been shown previously that the stimulatory component is constitutively expressed on the monocyte plasma membrane and is a protein or has a protein moiety. Here we showed that cd T-cell responses to the monocytes requires interaction with the T-cell receptor because Fab 1 fragments of a monoclonal antibody (mAb) that reacts with the d chain of the T-cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The proliferation of CD4 ϩ T cells is antigenindependent. Our observations are similar to the phenomenon known as the autologous MLR, where it was shown that bovine monocytes stimulate the proliferation of autologous ␥␦ T cells [32]. The effect of ADA addition is most prominent at low concentrations of monocytes, where the amount of proliferating CD4 ϩ T cells can be several-folds higher than in the absence of the enzymes (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The proliferation of CD4 ϩ T cells is antigenindependent. Our observations are similar to the phenomenon known as the autologous MLR, where it was shown that bovine monocytes stimulate the proliferation of autologous ␥␦ T cells [32]. The effect of ADA addition is most prominent at low concentrations of monocytes, where the amount of proliferating CD4 ϩ T cells can be several-folds higher than in the absence of the enzymes (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Studies of bovine γ/δ TCR-expressing cells have to date, for example, shown that these cells recognize conserved antigens induced by or derived from Theileria parva in an MHC-unrestricted fashion (28), present antigen to CD4-expressing cells and produce an array of cytokines known to influence the activities of antigen-presenting cells as well as CD4-expressing cells (29). It has also been shown that bovine γ/δ TCR-expressing cells can be stimulated to proliferate by autologous monocytes (30).…”
Section: Discussionmentioning
confidence: 99%
“…Function of these macrophages during pregnancy is not known but evidence exists to indicate a role in immunoprotection of the conceptus, 11–14 apoptosis, 4,10 trophoblast growth, 15 and parturition 5,16 . In sheep, it is possible that endometrial macrophages participate in the increase in number and granularity of γ δ T cells seen in endometrial luminal epithelium 20,21 because autologous monocytes can stimulate proliferation of bovine γ δ T cells 22 …”
Section: Discussionmentioning
confidence: 99%